PREVALENCE, MANAGEMENT, AND OUTCOME OF BELLS PALSY : A COMPREHENSIVE SYSTEMATIC REVIEW - Permata Sari, Mirna Ayu; Mardika, Cahyanu (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Bell’s palsy, also called idiopathic facial paralysis, is defined as an acute-onset, isolated, unilateral, lower motor neurone facial weakness. The reported annual incidence varies in different parts of the world with estimates varying between 11 and 40 per 100 000 people. The aim: The aim of this study to show about prevalence, management, and outcome of bell’s palsy. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Bell's palsy is a common but still controversial disease, with unknown etiology until now. Modern literature showed that up to 80 percent of the patients will recover without treatment.